Socio-Economic Status Determines Risk of Receptive Syringe Sharing Behaviors among Iranian Drug Injectors; A National Study - Assari, Shervin; Ahmadi, Khodabakhsh; Rezazade, Majid (Frontiers in Psychiatry, 2015)
Background: Although needle and syringe sharing is one of the main routs of transmission of HIV in several countries in the middle east, very little is known about how socioeconomic status of injecting drug users (IDUs) is linked to the receptive syringe sharing behaviors in these countries. Aim: To study socioeconomic correlates of receptive needle and syringe sharing among IDUs in Iran. Methods: The study used data from the Unhide Risk Study, a national survey of IDUs. This study sampled 636 IDUs (91% male) via snowball sampling from eight provinces in Iran in 2009. Socio-demographic and drug use characteristics were collected. We used a logistic regression to determine factors associated with receptive needle and syringe sharing during the past six months. Results: From 636 IDUs enrolled in this study, 68% (n=434) reported receptive needle and syringe sharing behaviors in the past six months. Odds of receptive needle and syringe sharing in the past six months was lower among IDUs who were male (OR=0.29, 95% CI= 0.12 to 0.70), had higher education (OR=0.74, 95% CI=0.64 to 0.86) but higher among those who were unemployed (OR=4.05, 95% CI=1.50 to 10.94), and were single (OR=1.47, 95% CI=1.02 to 2.11). Conclusion: This study presented factors associated with risk of receptive needle and syringe sharing among Iranian IDUs. This information may be used for HIV prevention and harm reduction purposes. Socioeconomic status of Iranian IDUs may be closely linked to high risk injecting behaviors among them.